KEANEKARAGAMAN JENIS DAN PEMANFAATAN TUMBUHAN OBAT DI KAWASAN TAMAN NASIONAL LORE LINDU (TNLL) DI DESA MATAUE KECAMATAN KULAWI KABUPATEN SIGI - Arnold, Arnold; Harijanto, Herman; Sustri, Sustri (Jurnal Warta Rimba, 2017)
Nowadays  the utilization of traditional medicine by people is used as alternative medicine for themselves. The utilization of traditional medicine is one of local community culture that still exist especially in Mataue village.  The research aimed to find out the variety of medicinal plants in Lore Lindu National Park in Mataue village and its utilization. The reseach was conducted for three months beginning on February up to the month of April 2015, in Lore Lindu National Park in Mataue village Kulawi subdistrict Sigi district.  The method of the research was survey method by making path which to place the first swath done purposively and made in four (4) paths, each path consisted of  5 plots with size 20 m x 20 m, the space among plots in each path was 20 meter,  then the utilization, the kind of medicinal plants were known by doing non formal interview to the field guide, who utilized the medicinal plants, local midwives, trained traditional midwives and literature review.  The data gathered then descibed as about the utilization and then analized for deciding the Important Rate Index (INP) and Species Variety Index  (H’).  The result of the reseach found that there were 43 species of medicinal plants from 32 familes. The medicinal plants that dominated on tree level was Alstonia scholaris (L.) R.Br INP 92,43%, on pole level was Syzygium sp INP 48,67%, on stem level was  Rubus fraxinifolius Poir INP 32,06%, while the species that dominated on seed and undergrowth level was Selaginella with INP 16,11%. The variey index of medicinal plants on tree level was 1,79 (moderate), pole 2,07 (moderate), stem 2,60 (moderate), seed and undergrowth 3,48 (high). The variety index of medicinal plants in general categorized as moderate to high category. People in Mataue still  depending on medicinal plants in order to cure some  diseases by utilizing plants from the forest.Keywords:Traditional medicine,  Lore Lindu National Park, Important Rate Index,  Species